PENINGKATAN PROFESIONALISME GURU DAN KUALITAS PEMBELAJARAN BIOLOGI DI SEKOLAH MELALUI LESSON STUDY - Sriyati, Siti (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2006)
This research was done to investigate impact of lesson study in order to improve teachers professionalism and the quality of teaching learning process in Biology. Although lesson study has been conducted since the year of 2005 at numerous schools in Bandung, information on how far such activity does give impact to teacher as instructor and teacher as observer has not been uncovered. The research was undertaken by spreading questions to the instructor as well as the observer. Furthermore, quality of teaching learning process in the school was observed at SMP Lab. School and SMA Lab. School UPI. The research resulted in insight that through lesson study, teachers both served as instructor and observer can improve such competency as pedagogy, professional, personality, social as clearly indicated in â UU Guru dan Dosen No. 14 Tahun 2005â. However, for those teachers as observers, competency of pedagogy has not been significantly explored. Both the instructors and observers have not entirely user their KBM (teaching learning process) to conduct PTK (classroom action research). In addition, the KBM conducted in lesson study can improve quality of teaching learning process in the classroom based upon good interaction between students and teachers as well as among students (in or out the groups) during discussion and percentage of students who actively learned. Through model teaching learning process developed in lesson study, students are trained to improve their ability in scientific work and to connect biology concept to its application in daily life using local materials.Keyword : Teacherâs professionalism, lesson study, KBM (Teaching learning process),PTK (Classroom action research)